Terrestrial radiotherapy alters microhardness and surface micromorphology of dental restorative materials: an in vitro study - Walia, Apoorva; Mallya, Laxmish; MS, Athiyamaan; Lobo, Dilson; Shenoy, Ramya; Shenoy, Annapoorna (Frontiers in Oral Health, 2025)
BackgroundTherapeutic radiotherapy, commonly used in the treatment of head and neck cancers, may alter the mechanical and surface properties of restorative dental materials. Understanding these changes is essential for ensuring the long-term success of restorations in oncology patients.MethodsAn in vitro study was conducted on 90 disc-shaped specimens (n = 30 each) of three restorative materials: 3M™ Filtek™ Bulk Fill, Charisma Topaz One, and Cention N. Samples were subjected to two radiation protocols: (i) 70 Gy in 35 fractions (2 Gy/day), and (ii) 45 Gy in 5 fractions (9 Gy/day). Vickers microhardness testing and scanning electron microscopy (SEM) were performed 48 h post-irradiation.ResultsFiltek™ Bulk Fill exhibited the highest pre-radiation hardness (83.1 ± 2.3 HV), followed by Charisma Topaz One (74.5 ± 2.8 HV) and Cention N (69.8 ± 2.1 HV). After exposure to 70 Gy, a statistically significant reduction in microhardness was observed across all materials (p < 0.05), with Bulk Fill remaining the least affected (74.3 ± 2.1 HV). SEM images confirmed surface degradation in all groups, with varying degrees of filler particle exposure.ConclusionsIonizing radiation alters both microhardness and surface morphology of restorative materials, with bulk-fill composites demonstrating greater resilience. These findings warrant further investigation in vivo to understand long-term clinical implications.